Who is susceptible to perceive higher smog-induced health risk? Comparative analysis between physical and mental health dimensions. Issue 2 (7th February 2020) - Lu, Hui; Yue, Ailing; Liu, Xia
Abstract: Smog pollution can significantly affect the health of skilled workers. This paper explores the concept, structure and characteristics of smog-induced health risk perception. Based on face-to-face interviews with 30 skilled workers in a smog pollution area of China and quantitative analysis, we determined the dimensions of smog-induced health risk perception. The different effects of demographic variables on the dimensions of smog-induced health risk perception were investigated through 715 questionnaires distributed to skilled workers living in areas polluted by smog. The results showed that smog-induced health risk perception is a two-dimensional concept. We found that 86.3% of skilled workers perceived that physical health risk level was higher than mental health risk level. One-third of the population in most groups perceived higher degree of physical health risk than that of mental health risk, but the difference between physical and mental health risk for them was small. Moreover, skilled workers with a high level of smog-induced health risk perception were distributed mainly in groups of long employment duration, older skilled workers and skilled workers living in areas severely polluted by smog. Based on our results, we propose practical suggestions to help government, enterprises and skilled workers improve physical and mental health of skilled workers.